Pengaruh Pembelian Merchandise NCT terhadap Pembentukan Perilaku Konsumtif pada Mahasiswa FISIP ULM - Pramasti, Diva Khofiffah Zanuar; Khairussalam (Huma: Jurnal Sosiologi, 2024)
In maintaining their existence, K-Pop groups not only compete through their music but also merchandise that supports the promotion of the music they release.  This research aims to understand how rewards, stimulus and positive experiences from purchasing K-Pop merchandise can lead to repeat purchases. In addition, how individuals use social media as a tool to fulfill needs and get satisfaction rewards. Feeling satisfied because they have received rewards and achieved their needs, causes repeated merchandise purchasing behavior. So that it contributes to the formation of consumptive behavior of students seen from the perspective of behavioral exchange theory and Use and Gratification theory. This type of research uses qualitative research with a qualitative descriptive approach method, data collection techniques with observation, interviews, and documentation. The research informants were obtained by purposive sampling technique totaling 10 students who are fans of the NCT group at the Faculty of Social and Political Sciences. The results showed that the purchase of NCT merchandise was driven by several factors, including positive rewards (pleasure and satisfaction), emotional value in merchandise, as entertainment, self-reward, and external stimuli such as the influence of unboxing content or advertising. However, the research also found that the pleasant experience and satisfaction gained from purchasing NCT merchandise, has the potential to encourage consumptive behavior. Especially in terms of excessive financial spending and merchandise purchases that are often not planned, which affects student financial management. This study provides deep insight into the purchase of NCT merchandise, satisfaction obtained, and consumptive behavior.